2006
DOI: 10.1136/ard.2005.043992
|View full text |Cite
|
Sign up to set email alerts
|

The binding of lupus-derived autoantibodies to the C-terminal peptide (83-119) of the major SmD1 autoantigen can be mediated by double-stranded DNA and nucleosomes

Abstract: The SmD1(83-119) peptide is able to bind dsDNA and nucleosomes, and dsDNA or nucleosomes in applied reagents lead to an apparent reactivity of anti-dsDNA, anti-histone or nucleosome-specific antibodies with the SmD1(83-119) peptide in ELISA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Riemkasten and colleagues reported anti-SmD reactivity in 70.0% of SLE patients and in only 8.3% of controls using a SmD1 synthetic peptide [ 15 ]. This peptide, but not the full-length protein, has been shown to bind dsDNA contained in blocking reagents, which may result in the detection of anti-dsDNA antibodies in the SmD peptide ELISA [ 32 ]. In the present study we confirmed the dsDNA binding property of the SmD1 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Riemkasten and colleagues reported anti-SmD reactivity in 70.0% of SLE patients and in only 8.3% of controls using a SmD1 synthetic peptide [ 15 ]. This peptide, but not the full-length protein, has been shown to bind dsDNA contained in blocking reagents, which may result in the detection of anti-dsDNA antibodies in the SmD peptide ELISA [ 32 ]. In the present study we confirmed the dsDNA binding property of the SmD1 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…75 Another SmD1‐derived epitope comprising residues 83–119 has been identified and is recognized by a large number of SLE sera (see Table 3). 72 However, the high prevalence of reactivity in this setting is possibly a result of the DNA‐binding capacity of SmD1 83–119, which also binds anti‐dsDNA aAbs present in the sera of SLE patients 122,123 …”
Section: Clinically Relevant Epitopes (Peptides)mentioning
confidence: 99%
“…Among these models, (NZB × NZW) F1 mice are considered to be most representative of SLE in humans (8,21,38). Female (NZB × NZW) F1 mice are characterized by the production of antinuclear antibodies, including anti-dsDNA antibodies, and the development of severe immune complex-mediated glomerulonephritis (17,42). According to data from the Jackson laboratory, these female mice have an average life span of only 245 days (35 weeks) owing to the development of renal failure.…”
Section: Introductionmentioning
confidence: 99%